1989
DOI: 10.1172/jci113935
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin stimulates phospholipase C, Na+/H+ exchange, c-fos expression, and mitogenesis in rat mesangial cells.

Abstract: A recently described peptide hormone, endothelin, is a potent vasoconstrictor, but it is unclear whether endothelin has other biological actions. These experiments extend the range of biological actions of endothelin to stimulation of mitogenesis. Endothelin at low concentrations (0.1-10 nM) induced mitogenesis by quiescent rat glomerular mesangial cells in culture. Mitogenesis induced by endothelin was accompanied by activation of phospholipase C with increased inositol phosphate turnover and increments of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
210
0
3

Year Published

1990
1990
2011
2011

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 564 publications
(222 citation statements)
references
References 36 publications
9
210
0
3
Order By: Relevance
“…1, Table I). 1 pM ET-1, which generates only a monophasic, slow but sustained elevation of [Ca2+], (14), failed to induce mesangial cell contraction (Table I). In contrast, two concentrations of ET-1 (1.0 nM and 0.1 ,uM) that mobilize intracellular Ca2+ via activation of phospholipase C (14) increased the percentage of contracted cells above control (Table I) (Table I).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1, Table I). 1 pM ET-1, which generates only a monophasic, slow but sustained elevation of [Ca2+], (14), failed to induce mesangial cell contraction (Table I). In contrast, two concentrations of ET-1 (1.0 nM and 0.1 ,uM) that mobilize intracellular Ca2+ via activation of phospholipase C (14) increased the percentage of contracted cells above control (Table I) (Table I).…”
Section: Resultsmentioning
confidence: 99%
“…Using micropuncture, Badr and co-workers (10) documented increased glomerular afferent and efferent arteriolar resistance and a dramatic decline in the ultrafiltration coefficient, Kf, in response to ET- 1. Although the precise mechanism controlling Kf remains uncertain, the currently favored hypothesis is that contraction of mesangial cells, which are glomerular microvascular pericytes, decreases Kf by reducing filtration surface area (see 1 1-13 for review). We previously reported that ET-1 evokes two distinct patterns of Ca2' signaling in cultured rat mesangial cells ( 14). ET-l at 0.1-10.0 pM caused a modest but sustained elevation of [Ca2+]1 that depended on Ca2' entry.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Intensive studies have increased the knowledge on processing, pharmacological effects, receptors, signal transduction and antagonists of ETs [for review see 611]. As a mitogen, ET-1 has been reported to stimulate DNA synthesis in Swiss 3T3 fibroblasts [12][13][14], Rat-1 fibroblasts [15], rat mesangial cells [16] and glial cells [17].…”
Section: Introductionmentioning
confidence: 99%
“…It also stimulates in vitro proliferation of mesangial cells, fibroblasts, and vascular smooth muscle cells (2)(3)(4). Endothelin production in endothelial cells is augmented by thrombin, transforming growth factor P (TGFP), and interleukin-l (5,6), some of which are known to be up-regulated in rheumatoid arthritis (RA).…”
mentioning
confidence: 99%